Peningkatan Kualitas Generasi Sadar Kesehatan Reproduksi Remaja di Desa Pagaran Gala -Gala Kecamatan Panyabungan Selatan Kabupaten Mandailing Natal - Nasution, Helmi Wardah; Desi, Ferika; Batubara, Khoirunnisaa; Napitupulu, Ester Selfia (Jurnal Masyarakat Indonesia (Jumas), 2025)
Adolescents are residents in the age range of 10-19 years, according to the Regulation of the Minister of Health of the Republic of Indonesia Number 25 of 2014, adolescents are residents in the age range of 10-18 years and according to the Population and Family Planning Agency (BKKBN) the age range of adolescents is 10-24 years old and unmarried. The purpose of this activity is to improve the quality of the reproductive health conscious generation. Increasing their knowledge and skills, students can actively and independently maintain their reproductive health and become a generation that is aware of reproductive health. This community service activity uses the lecture and discussion method. The planning and preparation of this activity includes identifying respondents, preparing counseling materials and equipment, then the implementer identifies things that will be conveyed during counseling to teenagers. Counseling activities were carried out. The activity was attended The implementation of these activities included counseling activities on adolescent reproductive health, followed by a question-and-answer discussion with counseling participants and ended with an evaluation. The results of the evaluation after counseling showed that 85% of adolescents knew the definition of adolescents, 90% of adolescents knew the differences in adolescent physical changes, and 88% of adolescents knew the differences in adolescents' psychological changes.